Implementasi arsip elektronik dalam mendukung good goverment - Evi Zakiyah; Al Muhdil Karim (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
The changing of global paradigm in seeing the information of technology gives influence on governance. In realizing the transparency of public information by utilizing information technology, the role of electronic archives is very important in supporting it. This study uses a literature study on the application of electronic archives in a country about the implementation of archive management in support of e-Government where the result is a problem with absolutely no clear rules, laws and standards, less competent employees in the development of technological systems. The findings of this study which is an evaluation is expected to maximize its role in governance.